Customer Relationship Management (CRM): Building Solid Relationships for Business Sustainability - Ismail Razak (Journal Arbitrase : Economy, Management and Accounting, 2023)
In the era of globalization and increasingly fierce business competition, solid relationships with customers are the main key in maintaining business sustainability. This research aims to investigate the role and impact of implementing Customer Relationship Management (CRM) in building strong relationships for business sustainability. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of Customer Relationship Management (CRM) has a positive impact on the company. The use of CRM not only increases customer satisfaction through more personalized and responsive service, but also increases operational efficiency by automating business processes. Customer data integration helps companies understand customer preferences and behavior, opening up opportunities for increased sales and smarter marketing strategies. Thus, CRM is not just a technological tool, but is also the key to sustainable business growth and efficient operational continuity.